2021
DOI: 10.1002/cssc.202100200
|View full text |Cite
|
Sign up to set email alerts
|

Interface‐ and Surface‐Engineered PdO−RuO2 Hetero‐Nanostructures with High Activity for Hydrogen Evolution/Oxidation Reactions

Abstract: Active catalysts for HER/HOR are crucial to develop hydrogenbased renewable technologies. The interface of hetero-nanostructures can integrate different components into a single synergistic hybrid with high activity. Here, the synthesis of PdOÀ RuO 2 À C with abundant interfaces/defects was achieved for the hydrogen evolution reaction (HER) and hydrogen oxidation reaction (HOR). It exhibited a current density of 10 mA cm À 2 at 44 mV with a Tafel slope of 34 mV dec À 1 in 1 m KOH. The HER mass activity was 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…S8 and S9†). 50 Thus, the results of FESEM and TEM revealed that self-surface modification occurred during the course of the electrolysis. 31 The ICP-OES studies of the elute of the post catalyst confirmed that almost 70% of vanadium was leached into the solution (Table S5†), which led to an increase in the surface area of the material and exposed more and more active sites for the catalytic process.…”
Section: Resultsmentioning
confidence: 95%
“…S8 and S9†). 50 Thus, the results of FESEM and TEM revealed that self-surface modification occurred during the course of the electrolysis. 31 The ICP-OES studies of the elute of the post catalyst confirmed that almost 70% of vanadium was leached into the solution (Table S5†), which led to an increase in the surface area of the material and exposed more and more active sites for the catalytic process.…”
Section: Resultsmentioning
confidence: 95%
“…The i 0,m and i 0,s values for RuO 2 ‐Pt/C in 0.1 M KOH are 1833 mA/mg Pt,Ru and 1.8 mA/cm 2 Pt,Ru respectively. The HOR activity of RuO 2 ‐Pt/C was far better over Pt‐based reported catalysts in base media 51‐59 . For example, J. Zheng et al 50 reported i 0 value for Pt disk electrode was 0.21 mA.cm −2 in 0.1 M KOH.…”
Section: Resultsmentioning
confidence: 98%
“…The HOR activity of RuO 2 -Pt/C was far better over Pt-based reported catalysts in base media. [51][52][53][54][55][56][57][58][59] For example, J. Zheng et al 50 reported i 0 value for Pt disk electrode was 0.21 mA.cm À2 in 0.1 M KOH. The i 0,m value of RuO 2 -Pt/C in 0.1 M KOH is 29 and 8-fold higher than Ru-Pt-NPs/C and comm Pt/C respectively.…”
Section: Ph Universal Hor/her Activities Of Ruo 2 -Pt/c Catalystmentioning
confidence: 99%
“…[1d] However, PEMFCs operate in a strong acidic condition and rely on expensive Ptbased catalysts. [4] As a result; alkaline anion-exchange membrane fuel cells (AAEMFCs) and water electrolyzers have been regarded as a promising alternatives to the PEMFC-based devices. [5] Subsequently, the rapid development of AAEMFCs has motivated searches for active HOR/HER electrocatalysts in alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Samanta et al showed that HBE and oxophilic property may play equally important roles for HOR/HER in the alkaline medium. [4] Meanwhile, Speck et al demonstrated that maximizing the metal and metal oxide interface is crucial to HOR activity. [8d] Ruthenium is considered as an alternative to Pt in HOR/HER catalysts owing to the appropriate strength of RuÀ H bonds and lower price.…”
Section: Introductionmentioning
confidence: 99%